Geglückte Reintegration? Konferenzen als Spiegel internationaler Zusammenarbeit der Gesellschaft für Musikforschung 1947–1950 - Bartle, Christian; Flamm, Christoph (Die Musikforschung, 2023)
The process of German musicology’s rapprochement with the international scientific community after 1945 can be traced through the musicological meetings and conferences that took place both inside and outside Germany. The essay evaluates the international participation – of German musicologists internationally and international colleagues at conferences in Germany – as well as the reception of these conferences in Die Musikforschung up to 1950. The key figure behind these developments was Friedrich Blume. Although the statements and reports of the “Gesellschaft für Musikforschung” (GfM) do not indicate any willingness to come to terms with the Nazi past, within a few years foreign organisations were ready to reach out to their German colleagues again.